O direito à educação infantil e o Poder Judiciário: análise das decisões judiciais do Supremo Tribunal Federal (1988-2012) - Pinto, Isabela Rahal de Rezende (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2013)
This paper discusses the relationship between the right to early childhood education and the Judiciary, aiming to investigate and analyze the content of the collective judgments related to the right to early childhood education judged by Brazilian Supreme Court from the validity of Constitution of 1988 by the year 2012. To achieve the proposed objectives, it was used literature and documents having as object the judgments associated to the right to early childhood education decided by the Brazilian Supreme Court from 1988 until 2012. To deal with the documents, it was adopted the document analysis. Through this analysis it was observed that the Brazilian Supreme Court sustained unanimously and unequivocally that the access to early childhood education is a subjective public right or, in other words, it is the duty of the State (in the broad sense) to guarantee it to all children and if the State does not do so, it may be legally compelled to ensure the constitutional right to this stage of education. Despite the importance of the position taken by the Brazilian Supreme Court jurisprudence , it was inferred, based on the bibliographical references, that the court decisions were well founded theoretically and legally but they were not under the educational perspective.